"DUDE UR GUNNA BE A GREAT TEACHER YO": Cultivating Diverse Englishes Through Chatroom Discussions Between Preservice Teachers and Urban High School Youth. Issue 4 (4th July 2018) - Garcia, Antero; Seglem, Robyn
ABSTRACT: This article examines the potential for creating an alternative learning context using digital tools in English classrooms to better support the identities and language practices of diverse learners. We explore the role language plays in the relationships between preservice teachers in central Illinois and their 10th-grade partners in Los Angeles. Through discourse analysis of online chatroom transcripts, we found that intertextuality and persona building through intentional language use were 2 tactics participants used to shape power dynamics in their relationships. This study provided preservice teachers with opportunities to build relationships with students different from themselves, gain a deeper understanding of the language practices of youth, and explore power structures in schools.